Digital Innovation: Book Creator for Academic Speaking and Creativity in Higher Education - Arjulayana Arjulayana; Nargis Nargis; Dinda Hanifa Dewi; Suci Kintamani; Dara Dwi Kencana; Husna Khofifah Mulyadi; Nanda Faradilla Anwar (AL-ISHLAH: Jurnal Pendidikan, 2025)
Academic speaking remains a major challenge for many EFL students in higher education, often due to low confidence, limited vocabulary, and difficulty organizing ideas. This study explores the integration of Book Creator, a digital storytelling platform, to enhance students' academic speaking skills and creativity through multimodal learning. Using a Research and Development (RD) approach based on Rowntree’s instructional design model, the study involved 31 fourth-semester English Education students at Universitas Muhammadiyah Tangerang. The intervention incorporated digital storyboards using Book Creator across planning, development, and evaluation phases. Data were collected through classroom observation, pre- and post-speaking tests, and semi-structured interviews. A mixed-methods design was applied to analyze both quantitative and qualitative outcomes. The findings indicated an improvement in students’ speaking performance, with mean scores rising from 63.09 (pre-test) to 79.26 (post-test). The paired samples t-test yielded t(30) = 6.882, p = 0.06, showing a positive trend though not statistically significant at α = 0.05. Qualitative data revealed increased student motivation, confidence, and creativity, with students appreciating the ability to structure, rehearse, and visually present their ideas through multimodal features. The use of Book Creator as a digital storyboard tool fostered a student-centered environment that supported expressive, engaging, and reflective learning. While live practice remains essential, digital tools can complement and enhance academic speaking instruction in EFL contexts.